Analisis dampak input sektor industri dan sektor pertanian terhadap produk domestik regional bruto di Kabupaten/Kota Provinsi Jambi Wilayah Barat - Emilia, Emilia; Achmad, Erni; Mustika, Candra (Jurnal Paradigma Ekonomika, 2020)
The purpose of this study was to analyze the development of labor in the industrial and agricultural sectors as well as the regional GDP of the Western Jambi Province and to analyze the influence of the labor force of the industrial and agricultural sectors on the Jambi Province of the West Region. Descriptive analysis results show that during the period of 2010 to 2015 the value of GDP and labor in the agricultural sector and labor in the industrial sector in the city district in the western province of Jambi fluctuated with the highest average GRDP growth rate was Bungo, namely 8.05 % and lowest are 6.5% regencies, while agriculture sector labor with the highest average growth rate is 6.8% regency and lowest regency is Bungo regency -2.2% while for industrial sector workers with the highest average growth rate The regency is Bungo 79.5% and the lowest is Kerinci regency -6.01%. Based on the results of the regression showed that the employment of the agricultural sector and industrial sector workers have a significant positive effect on GRDP.